Increased Hemodynamic Load in Early Embryonic Stages Alters Endocardial to Mesenchymal Transition - Midgett, Madeline; López, Claudia S.; David, Larry; Maloyan, Alina; Rugonyi, Sandra (Frontiers in Physiology, 2017)
Normal blood flow is essential for proper heart formation during embryonic development, as abnormal hemodynamic load (blood pressure and shear stress) results in cardiac defects seen in congenital heart disease. However, the progressive detrimental remodeling processes that relate altered blood flow to cardiac defects remain unclear. Endothelial-mesenchymal cell transition is one of the many complex developmental events involved in transforming the early embryonic outflow tract into the aorta, pulmonary trunk, interventricular septum, and semilunar valves. This study elucidated the effects of increased hemodynamic load on endothelial-mesenchymal transition remodeling of the outflow tract cushions in vivo. Outflow tract banding was used to increase hemodynamic load in the chicken embryo heart between Hamburger and Hamilton stages 18 and 24. Increased hemodynamic load induced increased cell density in outflow tract cushions, fewer cells along the endocardial lining, endocardium junction disruption, and altered periostin expression as measured by confocal microscopy analysis. In addition, 3D focused ion beam scanning electron microscopy analysis determined that a portion of endocardial cells adopted a migratory shape after outflow tract banding that is more irregular, elongated, and with extensive cellular projections compared to normal cells. Proteomic mass-spectrometry analysis quantified altered protein composition after banding that is consistent with a more active stage of endothelial-mesenchymal transition. Outflow tract banding enhances the endothelial-mesenchymal transition phenotype during formation of the outflow tract cushions, suggesting that endothelial-mesenchymal transition is a critical developmental process that when disturbed by altered blood flow gives rise to cardiac malformation and defects.